2019
DOI: 10.20849/ijsn.v4i2.582
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Perceptions of Influenza Vaccination and Childhood Immunizations

Abstract: Background: After reviewing the literature on flu vaccinations and childhood immunizations, it was concluded that participation in these preventative measures is beneficial to health in increasing the chances of protection from specific diseases. Further studies show that not all college students receive them or plan to have their prospective children vaccinated. Purpose: The purpose of this study was to determine college students’ perception of influenza vaccination and childhood immunizations. Method: This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…4 The purpose of this research was to assess the prevalence of uptake of the seasonal annual influenza vaccination by the undergraduate student population attending a rural university in Texas and identify their personal attitudes, beliefs, and other barriers that hinder the receipt of the vaccination. Our findings suggest that being in the younger age group (18)(19)(20)(21)(22)(23)(24) and having health insurance can influence the uptake of annual seasonal influenza vaccinations. Having health insurance is a significant predictor of obtaining preventive services 16 , and being insured increases the likelihood of getting the annual influenza vaccination by the general population.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…4 The purpose of this research was to assess the prevalence of uptake of the seasonal annual influenza vaccination by the undergraduate student population attending a rural university in Texas and identify their personal attitudes, beliefs, and other barriers that hinder the receipt of the vaccination. Our findings suggest that being in the younger age group (18)(19)(20)(21)(22)(23)(24) and having health insurance can influence the uptake of annual seasonal influenza vaccinations. Having health insurance is a significant predictor of obtaining preventive services 16 , and being insured increases the likelihood of getting the annual influenza vaccination by the general population.…”
Section: Discussionmentioning
confidence: 78%
“…12,13,18,19 Additionally, one prior study has shown that college students that experience loneliness and small social networks are at higher risk for poor antibody response to the vaccine. 20 Previous research indicates that barriers to vaccine compliance in college students include the belief that the vaccine causes the illness 7 , has deleterious side effects or is ineffective 7,21,22 , that it is expensive 11,13 , is inconvenient 11,21 or that influenza does not pose a significant enough health risk. 7,11,21,23 Predictors of vaccine acceptance amongst college students include knowledge about the vaccine 21,23 , frequent interactions with children, employment in health care, parental education and influence 23,24 and off-campus residency.…”
Section: Introductionmentioning
confidence: 99%
“…Motivating college students to get the influenza vaccine is challenging (Cornally et al, 2013 ; NFID, 2017 ). Although healthy college-age students typically perceive themselves as being at low risk (Czyz et al, 2019 ), influenza (or simply, the flu) is serious and highly contagious. The influenza virus spreads quickly in the close quarters common on college campuses.…”
Section: Introductionmentioning
confidence: 99%
“…The flu is an important case from which to study vaccine hesitancy using the reasoned action approach (i.e., RAA). First, although college students underestimate the threat of the flu (Czyz et al, 2019 ; NFID, 2016 ), they are likely in close proximity with hundreds, if not thousands, of people daily in shared housing, classrooms, and face-to-face social interactions (e.g., study groups to sporting events). Second, seemingly healthy people can infect others one day before, and up to 5 to 7 days after, demonstrating flu symptoms (CDC, 2019 ).…”
Section: Introductionmentioning
confidence: 99%